Sphaeropteris guangxiensis Y. F. Gu & Y. H. Yan (Cyatheaceae), a new species of tree fern from Southern China - Gu, Yu-Feng; Morigengaowa; Jiang, Ri-Hong; Liu, Bao-Dong; Yan, Yue-Hong (Phytotaxa, 2021)
Nearly 103 species of Sphaeropteris are distributed in tropical area, of which three species are indigenous to China. Our previous molecular study of the genus in China showed that there is an undescribed species from Guangxi province which could be originated from natural hybridization. In this study, we carried out further morphological studies on the species of Sphaeropteris in China, and assessed the status of the new species. Here, we described and illustrated the new species as S. guangxiensis Y.F. Gu & Y.H. Yan.